Post-Adipose-Derived Stem Cells (ADSC) Stimulated by Collagen Type V (Col V) Mitigate the Progression of Osteoarthritic Rabbit Articular Cartilage - Brindo da Cruz, Isabele Camargo; Velosa, Ana Paula Pereira; Carrasco, Solange; dos Santos Filho, Antonio; Tomaz de Miranda, Jurandir; Pompeu, Eduardo; Fernandes, Tiago Lazzaretti; Bueno, Daniela Franco; Fanelli, Camila; Goldenstein-Schainberg, Cláudia; Fabro, Alexandre Todorovic; Fuller, Ricardo; et al. (Frontiers in Cell and Developmental Biology, 2021)
Collagen is essential for cartilage adhesion and formation. In the present study, histology, immunofluorescence, morphometry and qRT-PCR suggested that adipose-derived stem cells (ADSCs) stimulated by type V collagen (Col V) induces significantly increase of type II collagen (Col II) in the degenerative area of surgical-induced osteoarthritic rabbit articular cartilage (OA). In vitro, the effects of Col V on the proliferation and differentiation of ADSC were investigated. The expression of the cartilage-related genes, col2a1 and acan was significantly up-regulated and poul5fl down-regulated post-ADSC/Col V treatment. In vivo analyses revealed that post-ADSC/Col V treatment, rabbits showed typical signs of osteoarthritic articular cartilage regeneration by hematoxylin and eosin (H&E) and Safranin-O/fast-green. Immunohistochemical staining demonstrated that the volume of Col II fibers and the expression of Col II protein was significantly increased, and apoptosis Fas-ligand positive significantly decreased post-ADSC/Col V treatment. In conclusion, the expression Col II was higher in rabbits with surgical-induced osteoarthritic articular cartilage, hence ADSC/Col V may be a promising therapeutic target for OA treatment.